A Little Princess: strage 1 (400 headwords) - Burnett F. H. Frances (Oxford Bookworms Library)
Written by british-born author Frances Hodgson Burnett and first published in 1905, A Little Princess tells the story of young Sara Crewe, privileged daughter of a wealthy diamond merchant. All the other girls at Miss Minchins school treat Sara as if she truly were a princess. But when Captain Crewes fortune is sadly lost, Saras luck changes. Suddenly, she is treated no better than a scullery maid. Her own fierce determination to maintain her dignity and remain a princess inside has intrigued and delighted readers for more than a hundred years, even inspiring a sequel, Wishing for Tomorrow.